2010
DOI: 10.2319/011209-22.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Rapid Maxillary Expansion Followed by Fixed Appliances

Abstract: Objective: To evaluate the long-term changes in maxillary arch widths, overjet, and overbite in patients who were treated with rapid maxillary expansion (RME) followed by edgewise appliances. Materials and Methods: The material for the study consisted of study casts taken from 41 patients (19 males, 22 females) on four different occasions (before treatment, T1; after RME, T2; after treatment, T3; and during follow-up period, T4). The upper intercanine, interpremolar, and intermolar widths and overjet and overb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 17 publications
(16 reference statements)
0
51
0
2
Order By: Relevance
“…Average expansion (transverse dimension with greater increase in each patient) was 4.91 ± 1.54. The appliance remained passive in place as a retainer for at least three months,6 , 21 , 22 after which a removable retention plate was installed and used for three months associated with Edgewise appliances.…”
Section: Samplementioning
confidence: 99%
“…Average expansion (transverse dimension with greater increase in each patient) was 4.91 ± 1.54. The appliance remained passive in place as a retainer for at least three months,6 , 21 , 22 after which a removable retention plate was installed and used for three months associated with Edgewise appliances.…”
Section: Samplementioning
confidence: 99%
“…They were characterized by accumulation of a large magnitude of stretch force in a short time to open the non-fused sutures and obtain new bone formation. However, there are some problems encountered in clinical treatments, such as pain, limited expansion outcomes and post-expansion relapse [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Other authors have used the same sequence. 8 Although all the studies included the same protocol (expansion followed by an edgewise appliance therapy phase) that make them comparable, there is the question on how the edgewise therapy may have affected the long-term results of RME, such as better intercuspation or increase in arch width and perimeter after edgewise appliance therapy. For instance, the McNamara et al study 6 found a considerable increase in the mandibular intermolar and intercanine width and maxillary and mandibular arch perimeter.…”
Section: Commentary and Analysismentioning
confidence: 99%